Pharmacological exploration of traditional plants for the treatment of neurodegenerative disorders. (1st June 2020) - Wahid, Muqeet; Ali, Anam; Saqib, Fatima; Aleem, Ambreen; Bibi, Sumbal; Afzal, Khurram; Ali, Atif; Baig, Ayesha; Khan, Shujaat Ali; Bin Asad, Muhammad Hassham Hassan
Abstract : Alzheimer's disease (AD) is clinically characterized as memory deficits, altered behavior and impaired cognitive functions. The most important risk factor for AD is aging and mounting. Evidences suggested in different studies that traditionally used plants in Asia, China, and Europe significantly affect aging and AD involved neurodegeneration pathways. Research into ethnobotanicals for impaired memory and cognition has been burgeoned in last decades. The inclusion and exclusion criteria for the plant selection were based on reputed herbs recommended for treatment of neurological disorders and their scientific validation to cure neurodegenerative disorders. A range of traditional plants imparts effects via acetylcholinesterase activity, β‐amyloid peptide formation in plaques, neurotrophic factors and through antioxidant activity. On one side preclinical investigations identified promising drug candidates for AD, on the other side, clinical evidences are still pending. Presently, according to WHO, around more than 80% world population relay on natural remedies to cure their health related issues. Plants contain rich source of primary and secondary metabolites for improving health problems. Pharmaceutical industry is facing intriguing challenges like elevated cost and unendurable risk management due to the high burden of neurodegenerative disorders. A significant shift of drug discovery is being witnessed from synthetic moieties to herbal formulation.